2009
DOI: 10.1002/cphc.200900492
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitchable Fluorescent Nanoparticles: Preparation, Properties and Applications

Abstract: This minireview highlights recent advances of research dedicated to photoswitchable fluorescent nanoparticles and their applications. Recently, several strategies have been developed to synthesize nanoparticles with optically switchable emission properties: either fluorescence on/off or dual-alternating-color fluorescence photoswitching. The underlying mechanisms of fluorescence photoswitching enable many different types of photoswitchable fluorescent nanoparticles to change fluorescence colors, thus validatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 126 publications
(107 reference statements)
1
91
0
5
Order By: Relevance
“…However, our fluorescence setup is limited to probing MC-CD, not SP-CD. The presence of the electron injection decay channel (k inj ) on the titania surface will reduce the excited-state τ MC of the MC chromophore compared to that on the insulating zirconia surface: (6) This approach assumes that k R , k IC , and k isom are constant between the two metal oxide surfaces; studies have found this to be a reasonable assumption. 34,35 The time-resolved fluorescence decay curve for MC-CD-Ti after excitation at 532 nm is shown in Figure 5.…”
Section: Spiropyran−cyclodextrin Electron Injection Propertiesmentioning
confidence: 99%
“…However, our fluorescence setup is limited to probing MC-CD, not SP-CD. The presence of the electron injection decay channel (k inj ) on the titania surface will reduce the excited-state τ MC of the MC chromophore compared to that on the insulating zirconia surface: (6) This approach assumes that k R , k IC , and k isom are constant between the two metal oxide surfaces; studies have found this to be a reasonable assumption. 34,35 The time-resolved fluorescence decay curve for MC-CD-Ti after excitation at 532 nm is shown in Figure 5.…”
Section: Spiropyran−cyclodextrin Electron Injection Propertiesmentioning
confidence: 99%
“…At long wavelength edge (case c ) the species absorbing and emitting the low energy quanta are excited only. They do not exhibit FRET and their emission is highly polarized fl uorescent light intensities can oscillate between the FRET donor and acceptor emissions providing ON-OFF switching at each act of photoinduced transformations by light (Tian et al 2009 ;Giordano et al 2002 ;Jares-Erijman and Jovin 2003 ). Among different photochromes, diheteroarylethenes (Fig.…”
Section: Modulation By Lightmentioning
confidence: 99%
“…FRET-based NPs have been exploited for wavelength conversion, expansion of fluorescence lifetime, amplification of emission, and fluorescence photoswitching. Using FRET methods, NPs with improved photophysical properties have been widely used as highly sensitive bioprobes [77][78][79].…”
Section: Energy Transfermentioning
confidence: 99%